OPTIMALISASI PRODUKSI TAHU MENGGUNAKAN LINEAR PROGRAMMING METODE SIMPLEKS - Muhammad Nur Hidayat; Hawa Minriyadhil Jannah, Fiorenza Vania Seubelan, Paduloh (CV. Adiba Aisha Amira, 2025)
The main challenge in tofu production is the rising cost of soybean raw materials, which impacts efficiency and profitability. A quantitative approach was employed to develop a mathematical model based on Linear Programming, incorporating variables such as raw material availability, production capacity, and market demand. The model was solved using POM-QM Software. The analysis revealed that the optimal daily production for maximum profit of IDR 178,000 can be achieved with 2.55 cycles of white tofu production and 3.27 cycles of yellow tofu production per day. These findings highlight the importance of applying optimization methods to enhance efficiency and profitability.